A multi-level strategy for successively improved structural analysis of existing concrete bridges: examination using a prestressed concrete bridge tested to failure. Issue 1 (2nd January 2019) - Bagge, Niklas; Plos, Mario; Popescu, Cosmin
Abstract: This paper describes a multi-level strategy with increased complexity through four levels of structural analysis of concrete bridges. The concept was developed to provide a procedure that supports enhanced assessments with better understanding of the structure and more precise predictions of the load-carrying capacity. In order to demonstrate and examine the multi-level strategy, a continuous multi-span prestressed concrete girder bridge, tested until shear failure, was investigated. Calculations of the load-carrying capacity at the initial level of the multi-level strategy consistently resulted in underestimated capacities, with the predicted load ranging from 25% to 78% of the tested failure load, depending on the local resistance model applied. The initial assessment was also associated with issues of localising the shear failure accurately and, consequently, refined structural analysis at an enhanced level was recommended. Enhanced assessment using nonlinear finite element (FE) analysis precisely reproduced the behaviour observed in the experimental test, capturing the actual failure mechanism and the load-carrying capacity with less than 4% deviation to the test. Thus, the enhanced level of assessment, using the proposed multi-level strategy, can be considered to be accurate, but the study also shows the importance of using guidelines for nonlinear FE analysis and bridge-specific information.